Anxiety disorders and depression in patients undergoing cancer treatment using the hads scale: An integrative review - Amorim, Dara Kretschmer; Kamiyama, Samira Yukari; Eisenhardt, Larissa Soares; Santos, Paola Souza; Vasconcelos, Rosane Maria Andrade (Seven Editora, 2024)
Introduction: Psycho-Oncology as a subspecialty, which studies cancer patients and their physical, emotional, and psychological suffering. Such a state of anguish, when impactful, can lead to the development of mental disorders, such as anxiety and depression. Thus, with negative interference in daily life and worsening of quality of life, there may be difficulty in adhering to treatment, worsening the prognosis and survival of the patient. Objective: To analyze common mental disorders in cancer patients using the HADS scale. Methodology: The study consists of an integrative review of the scientific literature. The guiding question of the research determined by the PICO method was "What are the findings of the assessment of anxiety and depression by the Hospital Anxiety and Depression Scale (HADS) in patients undergoing cancer treatment?". Articles were searched in the following databases: LILACS, SciELO, PUBMED, Science Direct and CAPES Journals. The Health Sciences Descriptors used were: depression, anxiety, psycho-oncology, oncology and neoplasia. The included studies were full texts in English, Portuguese or Spanish, published between 2012 and October 2022. The use of the Hospital Scale for Anxiety and Depression (HADS) was used as a selection criterion. The data surveys were carried out in October and November 2022. The keywords were combined and the data found were read at the title level and, consequently, abstract. The articles selected by two independent evaluators were read in full and evaluated. In the end, the corpus consisted of 22 articles. Results and Discussion: The results of the review were subdivided into: symptoms of anxiety and depression, patients’ perception of care, and the sociodemographic profile of cancer patients with psychiatric disorders. There is a higher prevalence of anxiety and depression in female cancer patients when compared to the general population. Anxiety symptoms were more prevalent in the immediate aftermath of diagnosis, and lower levels of anxiety were found throughout the course of the course and treatment. In addition, the need for a multidisciplinary approach and early application of Palliative Care is emphasized, in order to alleviate the suffering of those involved, corroborating the improvement of mental health. Conclusion: Psychiatric anxiety and depression disorders in patients undergoing cancer treatment are relevant pathologies to be researched due to their impact on cancer treatment adherence. Thus, the importance of a comprehensive approach to the patient, whether in the physical or emotional aspects through multidisciplinary follow-up, is noted, enabling greater well-being for the patient, resulting in the best treatment according to the need. Thus, we emphasize the need for further research on the subject, in order to update the findings according to the presence of new articles. DOI:https://doi.org/10.56238/sevened2023.006-140